2011
DOI: 10.1021/bc100442q
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Molecular-Mimicry-Based Ligands for Cholera Diagnostics using Magnetic Relaxation

Abstract: When covalently bound to an appropriate ligand, iron oxide nanoparticles can bind to a specific target of interest. This interaction can be detected through changes in the solution's spin-spin relaxation times (T2) via magnetic relaxation measurements. In this report, a strategy of molecular mimicry was used in order to identify targeting ligands that bind to the cholera toxin B subunit (CTB). The cellular CTB-receptor, ganglioside GM1, contains a pentasaccharide moiety consisting in part of galactose and gluc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
8
1

Year Published

2011
2011
2016
2016

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 44 publications
(114 reference statements)
0
8
1
Order By: Relevance
“…Using our competition method, we found that the K D of the dextran–CTB interaction is 4.9 μ M . This value is substantially lower than the value we previously determined using SPR (14 m M ) 28. In that study, CTB was immobolized to the SPR gold plate using a ganglioside as a linker.…”
Section: Methodscontrasting
confidence: 58%
See 1 more Smart Citation
“…Using our competition method, we found that the K D of the dextran–CTB interaction is 4.9 μ M . This value is substantially lower than the value we previously determined using SPR (14 m M ) 28. In that study, CTB was immobolized to the SPR gold plate using a ganglioside as a linker.…”
Section: Methodscontrasting
confidence: 58%
“…Next, we utilized the bMR‐nanosensor‐based competition assay to study the interaction between toxins and small molecules. Recent reports describe the interaction of doxorubicin with the tetanus toxin C fragment (TTC)27 and galactose or dextran with cholera toxin B subunit (CTB) 28. The study of these interactions is important for the development of small‐molecule‐based therapeutics.…”
Section: Methodsmentioning
confidence: 99%
“…Carbohydrates have previously been used on the surface of functional nanoparticles to enhance cellular uptake efficiency and specicity. 23,85,86 Overexpression of specic mannose receptors on cancer cells has been investigated as target for therapeutics delivery, in a number of reports on cell lines such as MCF-7/Adr-res (breast cancer), SKOV-3 (ovarian adenocarcinoma), B16F10, B16F1, (murine melanoma), A549 (lung cancer), and A498 (kidney cancer). 53 Firstly, the cytotoxicity of IONPs and polymer functionalized IONPs was investigated for two different cell lines (in human lung broblast (MRC 5) and lung cancer cell (A549 cells)) using a standard method: Alamar Blue assay.…”
Section: Mri Relaxivity Measurements On Aqueous Dispersions Of Ionps ...mentioning
confidence: 99%
“…Recent reports describe the interaction of doxorubicin with the tetanus toxin C fragment (TTC) [27] and galactose or dextran with cholera toxin B subunit (CTB). [28] The study of these interactions is important for the development of small-molecule-based therapeutics. For the TTCdoxorubicin interaction, a doxorubicin-carrying iron oxide nanoparticle was designed.…”
mentioning
confidence: 99%
“…This value is substantially lower than the value we previously determined using SPR (14 mm). [28] In that study, CTB was immobolized to the SPR gold plate using a ganglioside as a linker. Likely, this approach may block sites at which dextran binds, therefore affecting the interaction between CTB and dextran.…”
mentioning
confidence: 99%